Effects of oxygen micro/nano bubble water on growth of baby cos lettuce Twitty variety in hydroponics - Tuikhom, Jarrumon; Sritontip, Chiti; Sritontip, Parinyawadee; Samlitoemsiri, Thiparat (Health Science, Science and Technology Reviews, 2024)
The effect of oxygen micro/nanobubbles in water on plant growth of baby cos lettuce Twitty variety in hydroponic cultivation were investigated. The experiment design was a completely randomize design (CRD). There are 4 treatments and 4 replications: 1) tap water (control), 2) macrobubbles (MBs), 3) micro/nanobubbles (MNBs), and 4) nanobubbles (NBs). The experiment was conducted between August and September 2023 for 28 days. There was no statistical difference in stem height, stem diameter, leaf width, leaf chlorophyll fluorescence, leaf nitrate, root fresh weight, and root dry weight. Whereas, the use of macrobubble and micro/nanobubble water had higher leaf width and root length than tap water and nanobubbles use. Nanobubble water use had the highest leaf length, leaf fresh weight, leaf dry weight, and total fresh weight per plant. In addition, the use of macrobubble water, micro/nanobubble water, and nanobubble water had a higher number of leaves, stem fresh weight than tab water. While, the use of micro/nanobubble water and nanobubble water enhanced the leaf greenness index and total dry weight per plant, which was higher than tap water and macrobubbles use.